Entry of criminals in parliament and legislatures - Deficiencies of laws and remedies - Nath, Kamaleshwar (1995)
"The author - himself a Lok Ayukta - critically examines the existing legal provisions relating to disqualification of candidates seeking entry into legislatures through election and points out their inadequacies and inconsistencies in preventing criminals from entering legislatures. While prescribing a remedy, he suggests setting up of a commission to determine the question of disqualification"
Keywords: Political coruption; Ethics; Political ethics - India; Legislators - India; Parliament